PERANCANGAN PRESENSI ABSENSI BERBASIS VISUAL BASIC DI PT NIKAWA DEPARTEMEN SPINNING 2 - melani, cucu; Abu Bakar Sidik, Haris; Ponco Subagyo, Catur (INFOKOM (Informatika & Komputer), 2024)
Attendance is one of the important activities in a company or agency that is useful for recording someone's attendance, this is useful for supporting operational activities in a company or agency. At PT Nikawa the attendance system is still carried out manually, namely by filling in the attendance book with the names and signatures where this method often results in invalid written attendance data until the event of manipulation of attendance data by employees. The purpose of this research is to build a desktop-based computerized attendance attendance system with the application of Visual Basic. The results of this study indicate that with the system that has been built, attendance admins were helped by the problems encountered, recording employee attendance data more precisely and quickly.